2003
DOI: 10.1165/rcmb.2002-0310oc
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Genes in Human Alveolar Macrophages Infected with Virulent or AttenuatedMycobacterium tuberculosis

Abstract: Tumor necrosis factor (TNF)-alpha-dependent apoptosis of alveolar macrophages (AM) after infection with avirulent Mycobacterium tuberculosis (Mtb) results in bacillary death and the destruction of a growth niche for the pathogen. This response is minimized after infection with virulent strains of Mtb. To study the genetic control of Mtb-induced apoptosis, we used microarrays to interrogate the expression profile of infected human AM. Although we found variation in gene expression between different donors of AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 39 publications
2
70
1
Order By: Relevance
“…Several in vitro studies have demonstrated that alveolar macrophages undergo apoptosis following infection with M. tuberculosis [2][3][4][5][6][7][8], and apoptosis of these infected macrophages may benefit the host by eliminating the favorable environment for bacterial growth [4,5]. Furthermore, these in vitro studies have also demonstrated that infected macrophage apoptosis was TNF-a dependent, and virulent strains, such as H37Rv, induce lesser macrophage apoptosis than the isogenic avirulent strain H37Ra [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro studies have demonstrated that alveolar macrophages undergo apoptosis following infection with M. tuberculosis [2][3][4][5][6][7][8], and apoptosis of these infected macrophages may benefit the host by eliminating the favorable environment for bacterial growth [4,5]. Furthermore, these in vitro studies have also demonstrated that infected macrophage apoptosis was TNF-a dependent, and virulent strains, such as H37Rv, induce lesser macrophage apoptosis than the isogenic avirulent strain H37Ra [5].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using in vitro systems, it has been shown that virulent strains induce less macrophage apoptosis than non-virulent strains [5,6]. Tumor necrosis factor-alpha (TNF-a) and nitric oxide (NO) are the most important pro-apoptotic mediators in this process [6,7], while Bcl-2 is the most significant anti-apoptotic molecule [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several candidate genes have been proposed to be associated with susceptibility for pulmonary TB [46][47][48][49]. Using these candidate genes, the quest for polymorphisms associated with disseminated disease has begun.…”
Section: Host Geneticsmentioning
confidence: 99%
“…The relevance of intracellular growth to strain virulence is supported by recent studies indicating that so-called ''hypervirulent strains,'' identified by molecular fingerprinting as being responsible for outbreak ''clusters'' of active tuberculosis, grow more rapidly within human phagocytes than do nonclustered isolates (11,12). Although differences in the interactions of M. tuberculosis strains of varying virulence with human phagocytes have been assessed using focused gene expression arrays (13,14),…”
mentioning
confidence: 99%